Makerspace in STEM for girls: a physical space to develop twenty-first-century skills - Sheffield, R.; Koul, R.; Blackley, Susan; Maynard, N. (Taylor and Francis, 2017)
Makerspace has been lauded as a new way forward to create communities, empower students and bring together enthusiasts of all ages and skill levels “to tinker” and create. Makerspace education has been touted as having the potential to empower young people to become agents of change in their communities. This paper examines how a Makerspace approach can capture the imagination and creativity of female primary school students, and engage them in integrated STEM-based projects. The study scaffolded female tertiary undergraduate students to mentor small groups of girls to complete a project in a STEM Makerspace situated in classrooms. The data generated and analysed from this study were used to determine how Makerspace STEM-based projects were enacted, how they engaged and supported the girls’ learning, and considers the future of a Makerspace approach as a way to progress integrated STEM education.